2017
DOI: 10.3390/nu9050429
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Magnesium Supplementation on Subjective Anxiety and Stress—A Systematic Review

Abstract: Background: Anxiety related conditions are the most common affective disorders present in the general population with a lifetime prevalence of over 15%. Magnesium (Mg) status is associated with subjective anxiety, leading to the proposition that Mg supplementation may attenuate anxiety symptoms. This systematic review examines the available evidence for the efficacy of Mg supplementation in the alleviation of subjective measures of anxiety and stress. Methods: A systematic search of interventions with Mg alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 79 publications
(109 reference statements)
1
53
0
5
Order By: Relevance
“…Our findings are consistent with previous studies on the association between serum magnesium concentrations and cognition in both animal and human studies (Allaert et al, 2016;Serefko et al, 2016;Balmus et al, 2017;Boyle et al, 2017;Iolascon et al, 2017;Kirkland et al, 2018). In a case-control study of 30 patients (15 with Alzheimer's disease and 15 with mild cognitive impairment) and 15 control participants, lower magnesium concentrations were found among patients with Alzheimer's disease and mild cognitive impairment (Balmus et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous studies on the association between serum magnesium concentrations and cognition in both animal and human studies (Allaert et al, 2016;Serefko et al, 2016;Balmus et al, 2017;Boyle et al, 2017;Iolascon et al, 2017;Kirkland et al, 2018). In a case-control study of 30 patients (15 with Alzheimer's disease and 15 with mild cognitive impairment) and 15 control participants, lower magnesium concentrations were found among patients with Alzheimer's disease and mild cognitive impairment (Balmus et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Anxiety and depression are mediated by dysfunctional glutaminergic neurotransmission and there is thus a rationale for an effect of magnesium on these outcomes. Supplementation studies with magnesium alone or in combination with other nutrients has been recently reviewed and the conclusion has been, in spite of some methodological weaknesses, that magnesium can be a useful adjunct to manage mild anxiety symptoms [209]. For example, magnesium lactate (300 mg), associated with vitamin B6, was found as effective as a pharmacological anxiolytic in improving anxiety scale scores in mildly anxious subjects [210] and a recent intervention trial found that in 264 healthy stressed subjects with low magnesaemia, supplementation with 300 mg magnesium daily resulted in reduced stress scores in a few weeks.…”
Section: Supplementation With Vitamin C Iron Magnesium or Zinc And mentioning
confidence: 99%
“…In a systematic review including 18 studies, the effect of Mg on different types of anxiety was investigated. Mg intake on postpartum anxiety was not effective, but it has been suggested to be effective in other types (Boyle et al, 2017). The cross-sectional studies examining the relationship between diet Mg intake and anxiety are limited.…”
Section: Discussionmentioning
confidence: 93%
“…According to the studies, one possible mechanism on the relationship between Mg and mood disorders is thought to be that Mg's inhibiting effect on N-methyl D-aspartate (NMDA) receptors. Mg blocks glutamate entry into the cell and reduces depressive symptoms (Boyle, Lawton, & Dye, 2017;Mlyniec et al, 2014). The other possible mechanisms are related with microbiota profile (Winther et al, 2015) and the limbic-hypothalamus-pituitary-adrenocortical axle (Hamada & Tsuruo, 1988).…”
Section: Introductionmentioning
confidence: 99%